Does a high level of job satisfaction reflect good working conditions? - Hofbauer, Reinhard; Schwingsmehl, Michael (Momentum Quarterly, 2017)
Job satisfaction has proved to be an important dimension of individual well-being and is taken into account in many modern welfare indices. For the measurement of job satisfaction there are objective as well as subjective indicators in use. By means of data of a population survey it can be shown that high values in single item questions on job satisfaction alone do not suffice to indicate good working conditions. Individual job satisfaction has to be considered as a complex phenomenon which is strongly influenced by processes of adaption and comparison.
Keywords: job satisfaction; working conditions; adaption; aspiration level; measuring satisfaction